Dendrites-free lithium metal anode enabled by synergistic surface structural engineering - Di, Jie (2022)
Lithium (Li) metal with high specific capacity and low redox potential is widely considered as a potential anode for lithium-ion batteries (LIBs) with high energy density. However, the catastrophic dendrites growth, “dead Li” formation, and surface passivation hinder its practical application. Herein, a selective artificial solid electrolyte interphase (SEI) layer (Li2Sx, x = 1, 2) protection strategy is adopted, where the tip sites passivation and the uniform Li nucleation in grooves are well combined, which enables reversible Li stripping/plating with high storage capacity and robust electrode framework. The grooves derived patterned array Li with selective Li2Sx artificial SEI (LS@A-Li) exhibit over 1800 h cycling life at 1.0 mA cm–2/1.0 mAh cm–2 and over 600 h even under 5.0 mA cm–2/10.0 mAh cm–2. The application feasibility of such LS@A-Li is also confirmed by coupling with commercial LiFePO4 and LiNi0.5Co0.2Mn0.3O2 (NCM523) in the full batteries. This work paves way for the large-scale application of Li metal anode in lithium-metal batteries with a facile and efficient fabrication process.